Employee job satisfaction factors: a case study of Al-Arafah Islami Bank Limited, Shantinagar Branch - Angon, Jayed Iqbal (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.